Historical foreword: Jean Dalibard, the magneto-optical trap, and the ascent of physics with cold atomic gases - Phillips, William (Comptes Rendus. Physique)
I present my personal perspective on the importance of the invention by Jean Dalibard of the magneto-optical trap (MOT), which has for many years been the “workhorse” of the field of laser cooling and cold atomic gases. I recount some of the history related to the MOT and argue that its invention enabled cold atomic gases to become the dominant part of Atomic, Molecular, and Optical (AMO) physics that it is today.